1994
DOI: 10.1152/jappl.1994.76.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Human muscle glycogen resynthesis after exercise: insulin-dependent and -independent phases

Abstract: To study the effects of glycogen depletion and insulin concentration on glycogen synthesis, gastrocnemius glycogen was measured with 13C-nuclear magnetic resonance at 4.7 T after exercise. Subjects performed single-leg toe raises to deplete gastrocnemius glycogen to 75, 50, or 25% of resting concentration (protocol I). Insulin dependence of glycogen synthesis was assessed after depletion to 25% with (protocol II) and without (protocol III) infusion of somatostatin to inhibit insulin secretion. After depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
205
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(224 citation statements)
references
References 0 publications
10
205
0
3
Order By: Relevance
“…In contrast, increased insulin sensitivity is undetectable in the early phase of the postexercise period (at 30 and 60 min) and becomes prominent at 180 min after exercise (48a). Consistent with these findings, Price et al (38) have shown in human muscle that postexercise glycogen repletion occurs in an insulin-independent manner for ϳ1 h after exercise, and thereafter insulin-dependent glycogen repletion becomes significant. Thus it appears that the increase in GDR after ES found in this study is likely due, at least in a large part, to the insulin-independent effect of muscle contraction, and the insulin-dependent effect may come into play particularly during the latter part of the poststimulation period.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, increased insulin sensitivity is undetectable in the early phase of the postexercise period (at 30 and 60 min) and becomes prominent at 180 min after exercise (48a). Consistent with these findings, Price et al (38) have shown in human muscle that postexercise glycogen repletion occurs in an insulin-independent manner for ϳ1 h after exercise, and thereafter insulin-dependent glycogen repletion becomes significant. Thus it appears that the increase in GDR after ES found in this study is likely due, at least in a large part, to the insulin-independent effect of muscle contraction, and the insulin-dependent effect may come into play particularly during the latter part of the poststimulation period.…”
Section: Discussionmentioning
confidence: 55%
“…Glycogen levels are depleted during exhaustive exercise (15). Restoration of these levels is in part independent of insulin action (15) and involves increases in both glucose uptake (33,34) and GS activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of these levels is in part independent of insulin action (15) and involves increases in both glucose uptake (33,34) and GS activity (35). However, to date the molecular mechanisms underpinning these events have been poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 The rapid phase only occurs when post-exercise muscle glycogen concentrations are below 30 -35 mmol/kg ww 43 and CHO is provided immediately post-exercise. 28 Hence, of the abovementioned dietary factors, CHO availability remains the key factor affecting both phases of postexercise glycogen synthesis and rate of recovery.…”
Section: Cho Availability: Amount and Timing Of Cho Ingestionmentioning
confidence: 99%